Methods of Modifying the Content of Glucosinolates and Their Derivatives in Sprouts and Microgreens During Their Cultivation and Postharvest Handling - Magdalena Michalczyk (International Journal of Food Science)
Sprouts and microgreens which belong to the Brassicaceae family contain significantly more glucosinolates than mature vegetables, and their composition often differs too. These plant growth stages can be a valuable supplement of the aforementioned compounds in the diet. The content and proportion of individual glucosinolates in sprouts and microgreens can be regulated by modifying the length and temperature of cultivation, the type of light, the use of mineral compounds, elicitation, primming, and cold plasma as well as storage conditions. The way in which sprouts are prepared for consumption affects the yield of glucosinolate hydrolysis. Genetic variation leading to different plant responses to the same factors (e.g., type of light) makes it necessary to conduct detailed studies involving species and variety diversity. Heat stress and the use of cold plasma appear to be fairly universal methods for increasing glucosinolate content. Studies on the use of light at different wavelengths do not provide unequivocal results. Despite experiments on the use of seed soaking solutions (e.g., sulfur and selenium compounds), there are no studies in the available literature on the effects of chemical and thermal seed disinfection methods on the glucosinolate content of the obtained sprouts and microgreens.